# Internal rate of return

## 1 Answer

$$NPV= -A+\sum_{t=0}^{T} \frac{EZU}{(1+EZF)^t}=-A+EZU(\frac{1-(1+EZF)^{T+1}}{1-(1+EZF)}) $$

\[=-A+\frac{EZU}{EZF}[(1+EZF)^{T+1}-1].\]

Hence

\[\frac{(1+EZF)^{T+1}-1}{EZF}=\frac{(NPV+A)}{EZU}.\]

This equation can not be explicitly solved in terms of $EZF$ and one needs to solve it numerically.

Erdos

4.6K

Join Matchmaticians Affiliate Marketing
Program to earn up to 50% commission on every question your affiliated users ask or answer.

- 1 Answer
- 130 views
- Pro Bono

### Related Questions

- Write a Proof
- Dynamic Systems of Differential Equations
- Integral of the fundamentla solution of the heat equation
- What is the integral of (x^2-8)/(x+3)dx
- Taylor Polynom/Lagrange form om the remainder term.
- Prove the trig identity $\sec x- \sin x \tan x =\frac{1}{\sec x}$
- Can we use the delta-ep def of a limit to find a limiting value?
- Week solution of the equation $u_t + u^2u_x = f(x,t)$